Respuesta :
Answer:
Option C
Step-by-step explanation:
we have
[tex]-6x^{2} -6x+12=0[/tex]
step 1
Group terms that contain the same variable, and move the constant to the opposite side of the equation
[tex]-6x^{2} -6x=-12[/tex]
step 2
Factor -6 leading coefficient'
[tex]-6(x^{2} +x)=-12[/tex]
step 3
Complete the square
Remember to balance the equation by adding the same constants to each side
[tex]-6(x^{2} +x+0.25)=-12-1.5[/tex]
[tex]-6(x^{2} +x+0.25)=-13.5[/tex]
step 4
Rewrite as perfect squares
[tex]-6(x+0.5)^{2}=-13.5[/tex]
simplify
[tex](x+0.5)^{2}=2.25[/tex]
Answer:
Step-by-step explanation:
the answer is c i just did it on usa
testprep